Efficacy and safety of 3CL protease inhibitors in patients with mild or moderate COVID-19: a systematic review and meta-analysis of randomized controlled trials - Nicole Jean Lee; Eric Shih Katsuyama; Christian Ken Fukunaga; Wilson Falco Neto; Ana Carolina Covre Coan; Hilaria Saugo Faria; Eduardo Alexandrino Medeiros (Virology Journal)
Abstract Background Remdesivir has been established as a safe treatment for patients with COVID-19. However, given the SARS-CoV-2 random mutations, 3CL protease inhibitors have been studied in recent randomized controlled trials. Therefore, this meta-analysis aims to compare 3CL protease inhibitors versus placebo in patients with mild to moderate COVID-19. Methods We systematically searched PubMed, Embase, and Cochrane Central for RCTs comparing the treatment regimens in patients with mild to moderate COVID-19. Outcomes of interest were the number of patients with symptomatic resolution, recovery rates, viral load change from baseline, alleviation rates, any adverse events, and serious/severe adverse events. Risk ratios (RRs) and hazard ratios (HRs) with 95% CI were calculated for binary outcomes, and standardized mean differences (SMDs) were calculated for continuous outcomes. R version 4.3.2 was used for statistical analysis with the random effects model. Results Ten studies were included, comprising 8,511 patients, of whom 4,654 (55.97%) received 3CL protease inhibitors. Follow-up ranged from 21 to 29 months. In our time-to-event analysis, 3CL protease inhibitors significantly increased the rate of alleviation (HR 1.17; 95% CI [1.09;1.25]; p < 0.01), and recovery rates (HR 1.18; 95% CI [1.11;1.26]; p < 0.01) in patients with mild to moderate COVID-19. However, 3CL protease inhibitors significantly reduced viral load at 72 h (SMD − 0.95; 95% CI [-1.23; -0.66]; p < 0.01) compared with placebo in these patients. There was no significant difference between groups in symptomatic resolution (RR 1.01; 95% CI [1.00;1.03]; p = 0.147). Conclusion 3CL protease inhibitors significantly reduced the change in the viral load and increased the rate of symptom alleviation and recovery, underscoring their importance as a potential therapeutic option.